A Critical Discourse Analysis of Oliver Prass’ Talk on “Antiasian Hate in the United States” in Kompas-TV - Try Mahendra Siregar; Erna Andriyanti; Sulis Triyono (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2021)
Racism is not only an internal issue of a country while discussing pluralistic society. The racism in the US must attain multitudes international attentions due to diversity of the people, including Asians with diverse races. The purposes of this study are to investigate how the ideology of racism is constructed through language and why the racism is occurred in pluralistic society of the US. The data for this study is two bilingual talks of Oliver Prass in KOMPAS TV. The CDA is adopted as tool to explore and discover racism ideology though language representation. The result on textual dimension with transitivity process depicts that racism ideology occurs in different forms to show effect of personal feeling and psychological effect from racist people toward the victims. In discursive dimension, to emphasize a hidden agenda of a discourse requires the speaker status and position during producing the language; for instance, as social activist, victims, and Indonesian. Then in social practices implies the reason why racism is existing; those are as a defense mechanism, economic anxiety, personality profile and power as well as authority abuse by the government that may lead to racism treatment on minorities by discrimination and negative prejudice.